QTL Mapping for Leaf Area of Tea Plants (Camellia sinensis) Based on a High-Quality Genetic Map Constructed by Whole Genome Resequencing - An, Yanlin; Chen, Linbo; Tao, Lingling; Liu, Shengrui; Wei, Chaoling (Frontiers in Plant Science, 2021)
High-quality genetic maps play important roles in QTL mapping and molecular marker-assisted breeding. Tea leaves are not only important vegetative organs but are also harvests with important economic value. However, the key genes and genetic mechanisms that regulate the development of tea leaves have not yet been elucidated. In this study, we performed whole-genome resequencing on ‘Jinxuan’, ‘Yuncha 1’ and their 96 F1 hybrid offspring. From the 1.84 Tb of original sequencing data, abundant mutation loci were identified, including 28,144,625 SNPs and 2,780,380 indels. By integrating the markers of a previously reported a genetic map, a high-density genetic map consisting of 15 linkage groups including 8956 high-quality SNPs was constructed. The total length of the genetic map is 1490.81 cM, which shows good collinearity with the genome. Twenty-five major QTL involved in leaf area were identified, and these regions have differentially expressed genes in large- and small leaf samples. Thirty-one pairs of newly developed indel markers located near QTL showed high polymorphism and had good discrimination between large and small leaf tea plant samples.